FORMULASI HANDSANITIZER SPRAY MINYAK ALPUKAT (Persea americana mill) TERHADAP BAKTERI Staphylococcus aureus - Ika Buana Januarti; Lisa Dzatul Mila; Aries Badrus Sholeh; Airina Maharyani; Monica Putri Anggraini (Nusantara Hasana Journal, 2025)
Hands are often the medium for contamination with pathogens. Bacteria on the palms of the hands belong to the normal flora group. Hand sanitizer spray is a hand sanitizer in the form of a spray for cleaning or removing germs on hands which contains several active ingredients derived from synthetic chemicals or natural ingredients. Natural ingredients that can be used as antimicrobial alternatives are found in avocados. The active substances contained in avocados are antibacterial, namely flavonoids, tannins, quercetin, alkaloids and saponins. Staphylococcus aureus bacteria are gram-positive micrococci bacteria that attack humans or are coagelase-positive. This research was carried out by making an avocado oil hand sanitizer preparation, then evaluating the formulation of the preparation and calculating the inhibitory power of Staphylococcus aureus bacteria. The media used was nutrient broth with inhibition power calculated using a caliper and analyzed using One Way Anova to compare each formulation. The results of the preparation meet the requirements of the organoleptic test, namely clear color, avocado aroma and liquid form. The preparation has good homogeneity with a pH value between 4.5-6.5. The inhibitory power obtained with medium strength is between 5-10. Avocado oil is an alternative for making hand sanitizer spray because it has active substances that inhibit the growth of bacteria.